Spanish government as lawmaker - Iwanek, Jan (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Spanish government as lawmaker The article presents constitutional law analysis of the Spanish government’s role in the lawmaking process. The government’s capacities in the following scopes are described: the initiation of legislative procedure, participation in the approval procedure (monarchical sanction), and the right to enact statutory legislative acts and regulatory (executive) acts. The role of the Council of State was depicted as an advisory body to the government in the lawmaking process, and the legal possibilities to initiate preventive and subsequent review by the Constitutional Tribunal. Key words: Spain, government, legislative process Abstrakt: Rząd hiszpański jako prawodawca W publikacji dokonano analizy prawnokonstytucyjnej roli rządu hiszpańskiego w procesie stanowienia prawa. Przedstawiono możliwości rządu w inicjowaniu procedury legislacyjnej, udział w postępowaniu zatwierdzającym (sankcja monarsza), prawo stanowienia aktów prawnych z mocą ustaw i aktów reglamentacyjnych (wykonawczych). Wskazano rolę Rady Stanu jako organu konsultacyjnego rządu w procesie prawotwórczym, a także prawne możliwości inicjowania kontroli prewencyjnej i następczej przed Trybunałem Konstytucyjnym. Słowa kluczowe: Hiszpania, rząd, postępowanie ustawodawcze